Protecting Data Privacy in Health Services Research - Medicine, Institute of; Services, Division of Health Care; Protection, Committee on the Role of Institutional Review Boards in Health Services Research Data Privacy (National Academies Press, 2000)
The need for quality improvement and for cost saving are driving both individual choices and health system dynamics. The health services research that we need to support informed choices depends on access to data, but at the same time, individual privacy and patient-health care provider confidentiality must be protected.